Gambaran Kejadian Anemia pada Ibu Hamil di Puskesmas Kembaran 1 - Sari, Gigih Retno; Haniyah, Siti; Triana, Noor Yunida; Ningrum, Ema Wahyu (Lembaga Pengembangan Kinerja Dosen, 2026)
Anemia during pregnancy is a condition commonly experienced by pregnant women. Insufficient iron intake or low iron levels in food is the main factor causing anemia in pregnant women. According to the World Health Organization (2019), the prevalence of anemia in pregnant women is 41.8%. The purpose of this study was to describe the characteristics and knowledge of pregnant women regarding anemia at Simpang Gambir Public Health Center, Mandailing Natal Regency, in 2021. This study used a descriptive design with a cross-sectional approach. The population consisted of all pregnant women at Simpang Gambir Public Health Center, Mandailing Natal Regency, totaling 53 people. The sample included all 53 pregnant women, using a total sampling technique. The analysis used was univariate analysis. The results showed that the majority of respondents were aged 26–35 years, totaling 35 people (66.%); the majority had a senior high school education, totaling 25 people (47.2%); the majority were employed, totaling 31 people (56.5%); and the majority were multigravida, totaling 33 people (62.3%). The level of knowledge of pregnant women about anemia was categorized as good in 13 people (24.5%), sufficient in 22 people (41.5%), and poor in 18 people (34.0%). It is expected that pregnant women will further improve their knowledge about anemia and apply it in daily life so that they can avoid anemia.